Sure
3Y + 5V = -12
5V = -12 -3Y
V = -12/5 -3Y/5
REPLACE IN 2ND EQU:
2Y - 3(-12/5-3Y/5) = -8
2Y + 36/5 +9Y/5 = -8
19Y/5 = -76/5
19Y = -76
Y = -76/19 = -4
THEN SOLVE FOR V
V = -12/5 - 3(-4)/5 = -12/5 +12/5 = 0
V = 0
2007-01-12 01:59:53
·
answer #1
·
answered by catarthur 6
·
1⤊
1⤋
3Y = -5V - 12 .......( subtract 5V from both sides of first equation)
Y= (-5/3)V - 4 ........( divide both sides by 3 to isolate Y)
......
2 ( (-5/3)V -4) -3V = -8 .......( SUBSTITUTE the Y = (-5/3)V -4 from the previous
into the second equation where you see a Y.)
(-10/3)V - 8 - 3V = -8 ...........( distribute the 2 into the parentheses. Basically,
multiply 2 by (-5/3)V and then by (-4). )
(-19/3)V -8 = -8 ....................(Add the V's on the left side)
(-19/3)V = 0 ...........................( Add 8 to both sides)
V = 0 .......................................( divide both sides by (-19/3) to find V)
Y = (-5/3) * (0) - 4 = 4...........( find Y by plugging in V=0 into the 2nd step up
there ^
2007-01-12 10:06:51
·
answer #2
·
answered by julka323 3
·
0⤊
0⤋
You can either do the substitution method or solve the equations simultaneously by multiplying equation 1 by 2 and equation 2 by minus 3.
The solution is v = 0 and y = -4
2007-01-12 10:00:51
·
answer #3
·
answered by edge 3
·
0⤊
1⤋
TAKE SECOND EQUATION:
2Y-3V=-8
2Y = 3V-8
Y = (3V-8) / 2
SUBSTITUTE INTO FIRST EQUATION:
3[(3V-8) / 2] + 5V = -12
(9V-24)/2 + 5V = -12
9V -24 + 10V = -24
19V - 24 = -24
19V = 0
V = 0
SUSTITUTE INTO SECOND:
2Y-3V=-8
2Y-3(0)=-8
2Y=-8
Y=-4
V={0}
Y={-4}
2007-01-12 10:12:49
·
answer #4
·
answered by aficionado210 2
·
0⤊
0⤋
3y+5v=-12..................................1
2y-3v=-8........................................2
multiply by 2 in EQUA. 1 and by 3 in EQUA.2
3y+5v=-12 X 2
2y-3v=-8 x3
6y+10V= -24
6Y -9V= -24
- + +
19V=0
V=0
SUBSTITUTE V=0 IN equa.1
3Y+0=-12
Y=-4
VERIFICATION:-
3(-4)+5(0)=-12
-12+0=-12
-12=-12
LHS=RHS
2007-01-12 10:26:37
·
answer #5
·
answered by srinu710 4
·
0⤊
0⤋